VALUE RELEVANCE ATAS INFORMASI AKUNTANSI SEBELUM DAN SESUDAH IFRS PADA SEKTOR PERTAMBANGAN DI INDONESIA - Vivian Jacob; Juniarti Juniarti Juniarti (Business Accounting Review, 2018)
The research objective was to examine the increase of value relevance of accounting information after International Financial Reporting Standards (IFRS) adoption in Indonesia. This Study used data from the mining sector listed in the Indonesia Stock Exchange (IDX) of the year 2007 to 2014. This Study used data from 13 companies mining for 8 years so that total number of observations in this study was 103. This study compared the circumstances prior to the adoption of IFRS compared with after the adoption of the IFRS using Stata application. In measuring the increase in value relevance, this research used variable EPS and BVPS in affecting the change in stock price. The best regression model in this study was model of fixed Effect both in the period before and after the adoption of the IFRS. This research showed that the value of EPS and BVPS were not significant in affecting changes in stock price. The result of this study showed that there was no increase in value relevance of accounting information in the mining sector.